A Double-Blind, Randomized, Placebo-Controlled Trial, Evaluating the Efficacy of Commiphora Mukul Cream in Improving Breast Engorgement in Breastfeeding Women: Efficacy of Commiphora Mukul cream in improving breast engorgement - Zolala, Shahrzad; Mojab, Faraz; Nahidi, Fatemeh; Khabazkhoob, Mahdi; Nasiri, Malihe (Iranian Journal of Pharmaceutical Sciences, 2020)
Breast engorgement is a common problem during breastfeeding that can lead to early discontinuation of breastfeeding. Commiphora Mukul (C. Mukul) is a medicinal plant with analgesic and anti-inflammatory compounds. The present study was conducted to determine the effect of C. Mukul on improving breast engorgement in breastfeeding women. This study was a double-blind, randomized, and placebo-controlled trial conducted with 100 breastfeeding women, whose symptoms of breast engorgement were randomly allocated to C. Mukul cream group or placebo. Both groups were to rub one fingertip of cream on each breast after nursing 8 times a day for 2 days. The breast engorgement symptoms )severity index = erythema + tension + pain erew assessed by the validated breast engorgement checklist. The severity of breast engorgement before the intervention was not significantly different between the two drug and placebo groups (breast erythema (P=0.78),tension (P=0.85) and pain (P=0.06)), but two days after the intervention, 60% of women in the drug group and 22 % of them in the placebo group scored zero in breast engorgement checklist, though there was a significant difference between the groups (P<0.001). No side effects were observed or reported in either group. According to the findings, Commiphora Mukul cream can improve breast engorgement.